Extracurricular Management Information System at SMPN Binakal Bondowoso Based on Website and WA Gateway - Iit Riyatul Hasanah; Abd Ghofur; Nur Azise (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The problem at SMPN Binakal Bondowoso is that several activity processes are carried out manually, namely they are still recorded in books, one of which is the management process in the extracurricular area. The impacts and consequences of using manual processes tend to require more time and effort than using automated processes or technology and can result in low efficiency in managing extracurricular activities, such as setting schedules, recording attendance and organizing events. The objectives of SMPN Binakal Bondowoso (ex-curricular) are additional activities carried out outside class hours, either at school or outside school. Extracurricular activities aim to ensure that students gain additional knowledge, skills and insight and shape their character according to their individual interests and talents. Extracurricular activities (excurriculars) are additional activities that take place outside of class hours, either at school or outside school. Extracurricular aims to ensure that students gain additional knowledge, skills and insight and help shape their character according to their individual interests and talents. The results of this research reveal that: 1) Extracurricular activities such as SMPN Binakal Bondowoso are capable of developing students' self-development. This is shown by the growth of students' self-confidence and increased communication skills. Extracurricular activities in the form of calligraphy activities can actually foster a sense of patience, thoroughness and creativity. This is proven by the ability to paint calligraphy with better, smoother patterns and various styles. 2) Increasing students' self-development, apart from internal factors, is also supported by the attention and policies of the school principal, such as providing training facilities and professional trainers. Meanwhile, the obstacles are insufficient practice time, inadequate supporting infrastructure. 3) the existence of an Extracurricular Management Information System at SMPN Binakal Bondowoso based on a website and WA Gateway provides information to parents of students that their students are taking part in extracurricular activities.